2021
DOI: 10.1055/s-0041-1731837
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality and Interactive Simulators on Dental Education Outcomes: Systematic Review

Abstract: In recent years, virtual reality and interactive digital simulations have been used in dental education to train dental students before interacting with real patients. Scientific evidence presented the application of virtual technology in dental education and some recent publications suggested that virtual and haptic technologies may have positive effects on dental education outcomes. The aim of this systematic review was to determine whether virtual technologies have positive effects on dental education outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 86 publications
(195 reference statements)
1
55
0
2
Order By: Relevance
“…Overall, the findings of our study clearly showed the effective role of VR simulators in improving the performance of dental students and increasing their satisfaction with this technology. As mentioned, the findings of other studies also confirm this[ 5 , 28 32 ]. The VR simulator has a wide range of applications in the fields of patient diagnosis and treatment and teaching students and dental professionals.…”
Section: Discussionsupporting
confidence: 81%
“…Overall, the findings of our study clearly showed the effective role of VR simulators in improving the performance of dental students and increasing their satisfaction with this technology. As mentioned, the findings of other studies also confirm this[ 5 , 28 32 ]. The VR simulator has a wide range of applications in the fields of patient diagnosis and treatment and teaching students and dental professionals.…”
Section: Discussionsupporting
confidence: 81%
“…VR uses customized and advanced software and hardware to create a digital 3D reality in which all user's senses are stimulated with computer-generated sensations and feedback [3]. Therefore, VR allows participants to experience simulated digital realities similar to those of physical reality, thus creating scenarios that are impossible to experience in the real world [4]. This newly created technology is increasingly applied in various areas of life, such as industry [5], medicine, rehabilitation and healthcare [6][7][8][9][10][11] or education [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of virtual simulators in professional education programs can allow students to refine their clinical skills without the risk of harming a patient during the learning process and, in this era of COVID-19, to certainly avoid potential infection [17]. Using VR, AR or MR simulators, a more realistic training could also support and reinforce ergonomics, thus improving the students' preclinical experience [79].…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of dental education is dedicated to teaching clinical psychomotor skills, and often, the dentist trains directly on the patient [17]. Currently, dental schools use realistic patient simulators with dental models incorporated to simulate a dental treatment [18].…”
Section: Applications In Pre-clinical Educationmentioning
confidence: 99%